“Enhancing Fraud Detection in Core Banking Systems Through Risk-Based Internal Controls and Forensic Auditing” (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The proliferation of Core Banking Systems (CBS), digital banking, cloud computing and real-time payment platforms has made financial fraud more sophisticated. Current fraud detection techniques are not effective anymore against new cyber assaults and complex financial crimes. This paper discusses the role of forensic auditing, risk-based internal controls and emerging technologies in enhancing fraud prevention in commercial banks. It discusses the application of forensic auditing with a combination of digital forensics, artificial intelligence (AI), machine learning, behavioural analytics, blockchain, and continuous auditing to improve fraud detection, fraud investigation, and regulatory compliance. The study also discusses contemporary issues in banking fraud such as insider threats, data privacy, legacy system integration, and regulatory requirements and suggests strategic measures to enhance fraud resilience. The findings indicate that the implementation of intelligent technologies with strong governance and forensic auditing mechanisms enable proactive fraud management, strengthen operational resilience, protect customer assets, and build trust in digital banking ecosystems.